ANALISIS KAPASITAS FUNGSIONAL RSU PKU MUHAMMADIYAH BANTUL DALAM PENANGGULANGAN BENCANA - Erwin Santosa; Tentrem Rianita (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2012)
PKU Muhammadiyah Bantul Hospital has been developing a disaster management hospital concept since 2008. A training through HOPE (Hospital Preparedness for Emergency and Disaster) has been conducted successfully. This research was aimed to measure the functional capacity of the PKU Muhammadiyah Bantul hospital in responding disaster and awareness of the staff as in Contingency Plan. The Hospital Safety Index criteria were used as the measurement instrument, which was consisted of five group indices. A descriptive survey technique was applied by means purposive sampling method. The samples were the staff in the Hospital Disaster Management Boards. A number of 61 questions were required by interview, observation and documents identification method. The hospital’s functional capacity index was calculated as 0.66. The scores varied for each group indices from 0.25 to 0.87. The highest score of 0.87 was obtained for group index of the operational plan, preventive maintenance and critical service restoration, whilst, the disaster emergency plan was assigned to the lowest score as 0.25. The mean score of all staffs about their job descriptions in contingency plan was 75.45 out of 100. Knowledge mean score of formulator staffs was 100 (high), while non formulator staffs was 69.7 (average). The core staff positioned in disaster management gained highest score (80.2), while the supporting staff was 74.7 (average). Hospital functional capacity index was 0.66 assessed in A class, indicating deemed to keep functioned during disaster situation. Awareness of the staffs, who designed Contingency Plan, were higher than the others. Deviation in awareness was also found among the staff involved in Contingency Plan. The manager level had a higher understanding in disaster preparedness if compared to the supporting staff.